Polarizing plate and display device

The circularly polarizing plate with a high puncture modulus retardation film and aligned protective film structure addresses hue changes in high-temperature environments, ensuring stable visibility.

JP7620134B2Active Publication Date: 2025-01-22SUMITOMO CHEM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024020467
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-04-11
Filing Date
2024-02-14
Publication Date
2025-01-22
Estimated Expiration
2038-11-26

AI Technical Summary

Technical Problem

Circularly polarizing plates using retardation films made from polymerizable liquid crystal compounds experience significant changes in reflected hue when exposed to high-temperature environments, particularly near the edges.

Method used

The circularly polarizing plate design includes a retardation film with a puncture modulus of 15 gf/mm or more, an adhesive layer, and a protective film with specific alignment to minimize hue changes, featuring a polymerizable liquid crystal compound layer and a polarizer with a protective film on one or both sides, and optionally a front plate.

Benefits of technology

The design maintains a small change in reflected hue before and after exposure to high temperatures, enhancing the stability and visibility of the polarizing plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620134000012
    Figure 0007620134000012
  • Figure 0007620134000013
    Figure 0007620134000013
  • Figure 0007620134000014
    Figure 0007620134000014
Patent Text Reader

Abstract

To provide a circularly polarizing plate having a retardation film, which shows a little change in reflection hues before and after the film is left in a high temperature environment.SOLUTION: There is provided a circularly polarizing plate in which a polarizing plate and a retardation film are laminated via a bonding layer, and which includes an adhesive layer on a surface thereof. The polarizing plate includes a polarizer. The retardation film is arranged between the polarizer and the adhesive layer. The retardation film includes two layers of retardation layers. The retardation layer includes a layer in which a polymerizable liquid crystal compound is cured. The retardation film has the piercing elastic modulus of 30 gf / mm or more and 150 gf / mm or less. The shape of the circularly polarizing plate is substantially the rectangular shape. The piercing elastic modulus is measured in a test using a needle having a tip with a diameter of 1 mmφ and 0.5 R at a piercing speed of 0.33 cm / sec. The test is performed in such a state that the retardation film is fixed between two plates with a circular hole having the diameter of 11 mm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate and a display device. [Background technology]

[0002] In recent years, image display devices, such as organic electroluminescence (hereinafter, also referred to as organic EL) display devices, have rapidly become widespread. Organic EL display devices are equipped with a circular polarizing plate that includes a polarizer and a retardation film (lambda / 4 plate). The placement of the circular polarizing plate can prevent reflection of external light and improve the visibility of the screen.

[0003] With the rise of organic EL display devices, there is a strong demand for thinner image display devices, and thus a demand for thinner circular polarizers is also growing. It has been considered to change from conventional retardation films made of resin films to retardation films made of liquid crystal compounds that can be made thinner (see, for example, Patent Document 1). Retardation films using polymerizable liquid crystal compounds are manufactured by coating a polymerizable liquid crystal compound on a substrate, orienting the compound, and fixing the orientation state by irradiating the compound with light as necessary. When a circular polarizer having a retardation film made of a polymerizable liquid crystal compound is placed in a high-temperature environment, there is a problem in that the hue of the circular polarizer changes from the initial state to blue or red. Specifically, when the circular polarizer is rectangular, the reflective hue near the four edges of the circular polarizer may change to blue or red, respectively. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-54093 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to solve the above problems and to provide a circular polarizing plate having a retardation film, which exhibits little change in reflected hue before and after being placed in a high-temperature environment. [Means for solving the problem]

[0006] [1] A circular polarizing plate having a polarizing plate and a retardation film, The retardation film includes a retardation layer, The retardation film has a puncture elastic modulus of 15 gf / mm or more, The puncture elastic modulus is an elastic modulus measured in a test using a needle with a tip diameter of 1 mmφ and a radius of 0.5 R at a puncture speed of 0.33 cm / sec. Circularly polarizing plate. [2] The circularly polarizing plate has a pressure-sensitive adhesive layer on a surface thereof, The polarizing plate has a polarizer, The retardation layer includes a layer in which a polymerizable liquid crystal compound is hardened, The circularly polarizing plate according to [1], wherein the retardation film is disposed between the polarizing plate and the pressure-sensitive adhesive layer. [3] The circularly polarizing plate according to [2], wherein the polarizer is formed from a layer of a cured liquid crystal compound. [4] The circular polarizer has a substantially rectangular shape; In the polarizing plate, a protective film is laminated on a surface of the polarizer opposite to a retardation film side, The protective film is a stretched film, The circularly polarizing plate according to [2] or [3], wherein the stretching direction of the protective film is substantially parallel to the short side direction of the circularly polarizing plate. [5] The circularly polarizing plate according to any one of [1] to [4], wherein the retardation film includes two retardation layers. [6] A circularly polarizing plate with a front plate, comprising the circularly polarizing plate according to any one of [1] to [5] and a front plate laminated together via an adhesive layer. [7] A display device, comprising the circularly polarizing plate according to any one of [2] to [4] laminated on a display element via the pressure-sensitive adhesive layer. Effect of the Invention

[0007] According to the present invention, it is possible to provide a circular polarizing plate having a retardation film, which exhibits little change in reflected hue before and after exposure to a high-temperature environment. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a schematic cross-sectional view showing a layer structure of a circular polarizing plate. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an example of a layer structure of an organic EL display device. [Diagram 3] FIG. 2 is a top view of a sample for evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Circular polarizing plate> The circular polarizing plate of the present invention includes a polarizing plate and a retardation film. The polarizing plate and the retardation film can be laminated, for example, via an adhesive layer. Examples of the adhesive layer include a pressure-sensitive adhesive layer and an adhesive layer described below. In the present invention, the polarizing plate refers to a laminate consisting of a polarizer and a protective film attached to one or both sides of the polarizer.

[0010] Hereinafter, an example of the layer structure of the circular polarizer of the present invention will be described with reference to FIG. 1. In FIG. 1, the adhesive layers for bonding the polarizer 10 and the protective films 11 and 12 are not shown. The circular polarizer 100 shown in FIG. 1(a) has a layer structure in which a polarizer 1 in which a first protective film 11 is laminated on one surface of the polarizer 10 and a second protective film 12 is laminated on the other surface of the polarizer 10, and a retardation film 2 including a layer 20 in which a polymerizable liquid crystal compound is cured are laminated via an adhesive layer 13. Furthermore, the circular polarizer 100 has an adhesive layer 14 on the surface of the retardation film 2 opposite to the polarizer 1. The adhesive layer 14 can be an adhesive layer for bonding to an organic EL display element or the like.

[0011] The circular polarizing plate 101 shown in FIG. 1(b) has a layer structure in which a polarizing plate 1 in which a first protective film 11 is laminated on one surface of a polarizer 10 and a second protective film 12 is laminated on the other surface of the polarizer 10, and a retardation film 2 are laminated via an adhesive layer 13. In the circular polarizing plate 101, the retardation film 2 has a layer structure in which a layer 20 of a cured polymerizable liquid crystal compound and a layer 21 of a cured polymerizable liquid crystal compound are laminated via an adhesive layer 15. Furthermore, the circular polarizing plate 101 has an adhesive layer 14 on the surface of the retardation film 2 opposite to the polarizing plate 1. The adhesive layer 14 can be an adhesive layer for bonding to an organic EL display element or the like.

[0012] The circular polarizer 103 shown in FIG. 1(c) has a layer structure in which a polarizer 1 having a first protective film 11 laminated on one surface of a polarizer 10 and a retardation film 2 are laminated via an adhesive layer 13. In the circular polarizer 103, the polarizer 1 is a polarizer having a protective film only on one surface of the polarizer 10. In the circular polarizer 103, the retardation film 2 has a layer structure in which a layer 20 of a cured polymerizable liquid crystal compound and a layer 21 of a cured polymerizable liquid crystal compound are laminated via an adhesive layer 15. Furthermore, the circular polarizer 103 has an adhesive layer 14 on the surface of the retardation film 2 opposite to the polarizer 1. The adhesive layer 14 can be an adhesive layer for bonding to an organic EL display element or the like.

[0013] As shown in Fig. 1, the retardation film may have one retardation layer or two retardation layers. The retardation film may have an alignment film for aligning a polymerizable liquid crystal compound during the manufacturing process. As shown in Fig. 1, the polarizing plate may have a protective film laminated only on one surface of the polarizer, or may have a protective film laminated on both surfaces.

[0014] The circular polarizing plate may have layers other than those shown in Fig. 1. Examples of layers that the circular polarizing plate may further have include a front plate, a light-shielding pattern, etc. The front plate may be disposed on the side of the polarizing plate opposite to the side on which the retardation film is laminated.

[0015] The light-shielding pattern can be formed on the surface of the front plate on the polarizing plate side. The light-shielding pattern is formed on the frame (non-display area) of the image display device, and can prevent the wiring of the image display device from being visually recognized by the user.

[0016] The shape of the main surface of the circular polarizing plate can be substantially rectangular. The main surface means the surface having the widest area corresponding to the display surface. Being substantially rectangular means that at least one of the four corners (corners) may be cut or rounded to be obtuse, a part of the end face perpendicular to the main surface may have a recessed part (notch) recessed in the in-plane direction, or a part of the main surface may have a hole cut out in the shape of a circle, an ellipse, a polygon, or a combination thereof.

[0017] The size of the circular polarizing plate is not particularly limited. When the circular polarizing plate is substantially rectangular, the length of the long side is preferably 6 cm or more and 35 cm or less, more preferably 10 cm or more and 30 cm or less, and the length of the short side is preferably 5 cm or more and 30 cm or less, more preferably 6 cm or more and 25 cm or less.

[0018] <Polarizing plate> In the present invention, the polarizing plate refers to a laminate consisting of a polarizer and a protective film attached to one or both sides of the polarizer. The protective film of the polarizing plate may have a surface treatment layer such as a hard coat layer, an antireflection layer, or an antistatic layer, which will be described later. The polarizer and the protective film can be laminated, for example, via an adhesive layer or a pressure-sensitive adhesive layer. The members of the polarizing plate will be described below.

[0019] (1) Polarizer The polarizer of the polarizing plate can be an absorption-type polarizer that absorbs linearly polarized light having a vibration plane parallel to its absorption axis and transmits linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). As the polarizer of the first layer, a polarizer in which a dichroic dye is adsorbed and aligned on a uniaxially stretched polyvinyl alcohol-based resin film can be suitably used. The polarizer can be produced, for example, by a method including the steps of: uniaxially stretching a polyvinyl alcohol-based resin film; dyeing the polyvinyl alcohol-based resin film with the dichroic dye to adsorb the dichroic dye; treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and washing with water after the treatment with the crosslinking liquid.

[0020] As the polyvinyl alcohol resin, a saponified polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers copolymerizable therewith can be mentioned. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.

[0021] In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acryloyl", "(meth)acrylate", etc.

[0022] The saponification degree of the polyvinyl alcohol resin is usually 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the polyvinyl alcohol resin is usually 1000 to 10000, preferably 1500 to 5000. The average polymerization degree of the polyvinyl alcohol resin can be determined in accordance with JIS K 6726.

[0023] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizer. The method for forming the polyvinyl alcohol-based resin is not particularly limited, and a known method is used. The thickness of the polyvinyl alcohol-based raw film is not particularly limited, but it is preferable to use one having a thickness of 5 to 35 μm in order to make the thickness of the polarizer 15 μm or less. More preferably, it is 20 μm or less.

[0024] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during a crosslinking treatment. The uniaxial stretching may also be performed in a plurality of these stages.

[0025] In the uniaxial stretching, the film may be stretched uniaxially between rolls having different peripheral speeds, or may be stretched uniaxially using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent or water. The stretching ratio is usually 3 to 8 times.

[0026] As a method for dyeing a polyvinyl alcohol-based resin film with a dichroic dye, for example, a method of immersing the film in an aqueous solution containing the dichroic dye is adopted. As the dichroic dye, iodine or a dichroic organic dye is used. It is preferable that the polyvinyl alcohol-based resin film is immersed in water before the dyeing process.

[0027] As a crosslinking treatment after dyeing with a dichroic dye, a method of immersing the dyed polyvinyl alcohol resin film in an aqueous solution containing boric acid is usually adopted. When iodine is used as the dichroic dye, the aqueous solution containing boric acid preferably contains potassium iodide.

[0028] The thickness of the polarizer is usually 30 μm or less, preferably 15 μm or less, more preferably 13 μm or less, even more preferably 10 μm or less, and particularly preferably 8 μm or less. The thickness of the polarizer is usually 2 μm or more, and preferably 3 μm or more. The inventors' study revealed that the change in hue of the circular polarizer is caused by the change in the retardation value of the retardation film. Furthermore, it was revealed that the change in the retardation value of the retardation film is caused by the stress when the polarizer shrinks in the dimension of the circular polarizer placed in a high temperature environment. Therefore, from the viewpoint of reducing the influence of the shrinkage of the polarizer, making the thickness of the polarizer 15 μm or less is effective in preventing the change in hue.

[0029] The polarizer may be formed from a layer of a cured liquid crystal compound, as described in, for example, JP 2016-170368 A. Specifically, a dichroic dye may be oriented in a cured film in which the liquid crystal compound is polymerized. As the dichroic dye, one having absorption in a wavelength range of 380 to 800 nm may be used, and it is preferable to use an organic dye. As the dichroic dye, for example, an azo compound may be used. The liquid crystal compound is a liquid crystal compound that can be polymerized while being oriented, and can have a polymerizable group in the molecule. This type of polarizer is obtained by applying a composition containing a liquid crystal compound and a dichroic dye onto an alignment film, and fixing the liquid crystal compound and the dichroic dye by irradiating with ultraviolet light or heating as necessary. In addition, as described in WO2011 / 024891 and JP 2018-120229 A, a polarizer may be formed from a dichroic dye having liquid crystal properties. In this way, forming a polarizer from a layer of a cured liquid crystal compound can contribute to reducing dimensional changes of the polarizer in a high-temperature environment, and is effective in preventing changes in hue.

[0030] When a polarizer including a layer of a cured liquid crystal compound is used as the polarizer, the thickness of the polarizer can be set to 500 nm or more and 3 μm or less.

[0031] (2) Protective film The circular polarizing plate of the present invention preferably has a protective film on at least one surface of the polarizer, and preferably has a protective film on the surface of the polarizer opposite to the retardation film side. When the circular polarizing plate is substantially rectangular and the protective film is a stretched film, it is preferable that the stretching direction of the protective film and the short side direction of the circular polarizing plate are substantially parallel. When the circular polarizing plate is substantially rectangular and the protective film is an unstretched film, it is preferable that the direction in which the tensile modulus is the largest in the plane of the protective film and the short side direction of the circular polarizing plate are substantially parallel. When the stretching direction (or the direction in which the tensile modulus is the largest) and the short side direction have such a relationship, the hue change of the circular polarizing plate tends to be small regardless of the direction of the slow axis of the retardation film. When the stretching direction (or the direction in which the tensile modulus is the largest) of the protective film is parallel to the short side, the contraction force in the stretching direction of the protective film due to the stretch relaxation of the polarizer and the protective film in a high temperature environment is smaller than when it is parallel to the long side, and it is considered that the hue change is small. The tensile modulus of elasticity is measured at 80° C. using, for example, an Autograph (registered trademark) (manufactured by Shimadzu Corporation, model number: AG-IS).

[0032] The stretching direction of the protective film and the short side direction of the circular polarizing plate being substantially parallel includes not only the case where they are strictly parallel, but also the case where the angle between them is 0±10°. The angle between the stretching direction of the protective film and the short side direction of the circular polarizing plate is preferably 0±5°. The unstretched film includes not only a non-stretched film, but also a substantially non-stretched film with a stretch ratio of 1.1 times or less.

[0033] The protective films laminated on both sides of the polarizer can be films made of a light-transmitting (preferably optically transparent) thermoplastic resin, for example, a polyolefin resin such as a chain polyolefin resin (such as a polypropylene resin) or a cyclic polyolefin resin (such as a norbornene resin); a cellulose resin such as triacetyl cellulose or diacetyl cellulose; a polyester resin such as polyethylene terephthalate or polybutylene terephthalate; a polycarbonate resin; a (meth)acrylic resin such as a methyl methacrylate resin; a polystyrene resin; a polyvinyl chloride resin; an acrylonitrile-butadiene-styrene resin; an acrylonitrile-styrene resin; a polyvinyl acetate resin; a polyvinylidene chloride resin; a polyamide resin; a polyacetal resin; a modified polyphenylene ether resin; a polysulfone resin; a polyethersulfone resin; a polyarylate resin; a polyamideimide resin; a polyimide resin, or the like.

[0034] Examples of linear polyolefin resins include linear olefin homopolymers such as polyethylene resins (polyethylene resins which are homopolymers of ethylene, and copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins which are homopolymers of propylene, and copolymers mainly composed of propylene), as well as copolymers composed of two or more types of linear olefins.

[0035] Cyclic polyolefin resin is a general term for resins polymerized with cyclic olefin as a polymerization unit, and examples thereof include resins described in JP-A-1-240517, JP-A-3-14882, JP-A-3-122137, etc. Specific examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers (typically random copolymers) of cyclic olefins and chain olefins such as ethylene and propylene, and graft polymers modified with unsaturated carboxylic acids or derivatives thereof, as well as hydrogenated products thereof. Among these, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers as cyclic olefins are preferably used.

[0036] The polyester resin is a resin having an ester bond, excluding the cellulose ester resin described below, and is generally made of a polycondensate of a polyvalent carboxylic acid or its derivative and a polyhydric alcohol. As the polyvalent carboxylic acid or its derivative, a divalent dicarboxylic acid or its derivative can be used, for example, terephthalic acid, isophthalic acid, dimethyl terephthalate, and dimethyl naphthalenedicarboxylate. As the polyhydric alcohol, a divalent diol can be used, for example, ethylene glycol, propanediol, butanediol, neopentyl glycol, and cyclohexanedimethanol. A representative example of the polyester resin is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol.

[0037] The (meth)acrylic resin is a resin whose main constituent monomer is a compound having a (meth)acryloyl group. Specific examples of the (meth)acrylic resin include poly(meth)acrylic acid ester such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (MS resin, etc.); copolymers of methyl methacrylate and a compound having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.). Preferably, poly(meth)acrylic acid C such as polymethyl (meth)acrylate is used. 1-6 A polymer containing an alkyl ester as a main component is used, and more preferably, a methyl methacrylate-based resin containing methyl methacrylate as a main component (50 to 100% by weight, preferably 70 to 100% by weight) is used.

[0038] The cellulose ester resin is an ester of cellulose and a fatty acid. Specific examples of the cellulose ester resin include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers thereof and those in which a part of the hydroxyl group is modified with another substituent are also included. Among these, cellulose triacetate (triacetyl cellulose) is particularly preferred.

[0039] Polycarbonate resins are engineering plastics made of polymers in which monomer units are bonded via carbonate groups.

[0040] It is also useful to control the retardation value of the protective film to a value suitable for an image display device such as a liquid crystal display device. For example, in an in-plane switching (IPS) mode liquid crystal display device, it is preferable to use a film having a substantially zero retardation value as the protective film. The substantially zero retardation value means that the in-plane retardation value Re(550) at a wavelength of 550 nm is 10 nm or less, and the absolute value of the thickness direction retardation value Rth at a wavelength of 550 nm is 10 nm or less. The absolute value of the thickness direction retardation value Rth at wavelengths of 480 to 750 nm is preferably 15 nm or less. In addition, in order to improve the visibility of the screen when a user wears polarized sunglasses or the like, the in-plane retardation value Re(550) at a wavelength of 550 nm may be 70 to 140 nm.

[0041] For example, depending on the mode of the liquid crystal display device, the protective film may be subjected to stretching and / or shrinking processing, etc., to impart a suitable retardation. For example, for the purpose of compensating for the viewing angle, a single-layer or multi-layer structure may be used as the protective film.

[0042] The thickness of the protective film is usually 1 to 100 μm, but from the viewpoints of strength, handleability, etc., it is preferably 5 to 60 μm, more preferably 10 to 55 μm, and even more preferably 15 to 40 μm.

[0043] The protective films attached to one or both sides of the polarizer may be made of the same or different thermoplastic resins, may have the same or different thicknesses, and may have the same or different retardation properties.

[0044] As described above, at least one of the protective films may have a surface treatment layer (coating layer) such as a hard coat layer, an antiglare layer, a light diffusion layer, an antireflection layer, a low refractive index layer, an antistatic layer, or an antifouling layer on its outer surface (the surface opposite to the polarizer). The thickness of the protective film includes the thickness of the surface treatment layer.

[0045] The protective film can be attached to the polarizer via, for example, an adhesive layer or a pressure-sensitive adhesive layer. As the adhesive for forming the adhesive layer, a water-based adhesive, an active energy ray-curable adhesive, or a heat-curable adhesive can be used, and preferably, a water-based adhesive or an active energy ray-curable adhesive can be used. As the pressure-sensitive adhesive layer, the one described below can be used.

[0046] Examples of the aqueous adhesive include an adhesive made of an aqueous polyvinyl alcohol resin solution, an aqueous two-liquid urethane emulsion adhesive, and the like. Among them, an aqueous adhesive made of an aqueous polyvinyl alcohol resin solution is preferably used. Examples of the polyvinyl alcohol resin include a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, a polyvinyl alcohol copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith, and a modified polyvinyl alcohol polymer in which the hydroxyl groups of these are partially modified. The aqueous adhesive may contain a crosslinking agent such as an aldehyde compound (such as glyoxal), an epoxy compound, a melamine compound, a methylol compound, an isocyanate compound, an amine compound, or a polyvalent metal salt.

[0047] When a water-based adhesive is used, it is preferable to carry out a drying step for removing water contained in the water-based adhesive after laminating the polarizer and the protective film. After the drying step, a curing step may be carried out, for example, at a temperature of 20 to 45° C.

[0048] The active energy ray-curable adhesive is an adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, and is preferably an ultraviolet ray-curable adhesive.

[0049] The curable compound may be a cationic polymerizable curable compound or a radical polymerizable curable compound. Examples of the cationic polymerizable curable compound include an epoxy compound (a compound having one or more epoxy groups in the molecule), an oxetane compound (a compound having one or more oxetane rings in the molecule), or a combination thereof. Examples of the radical polymerizable curable compound include a (meth)acrylic compound (a compound having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radical polymerizable double bond, or a combination thereof. A cationic polymerizable curable compound and a radical polymerizable curable compound may be used in combination. An active energy ray curable adhesive usually further includes a cationic polymerization initiator and / or a radical polymerization initiator for initiating the curing reaction of the curable compound.

[0050] When laminating the polarizer and the protective film, at least one of the laminating surfaces may be subjected to a surface activation treatment in order to enhance adhesion. Examples of the surface activation treatment include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), flame treatment, ozone treatment, UV ozone treatment, and ionizing active ray treatment (ultraviolet ray treatment, electron beam treatment, etc.); and wet treatments such as ultrasonic treatment using a solvent such as water or acetone, saponification treatment, and anchor coat treatment. These surface activation treatments may be performed alone or in combination of two or more.

[0051] When protective films are attached to both sides of the polarizer, the adhesive for attaching these protective films may be the same kind of adhesive or different kinds of adhesives.

[0052] Instead of the protective film, a protective layer may be formed on at least one surface of the polarizer. The protective layer can be formed on the polarizer without an adhesive layer or a pressure-sensitive adhesive layer, that is, the protective layer can be formed in contact with the polarizer. The protective layer can be a layer containing a (meth)acrylic resin or a layer containing a water-based resin.

[0053] The layer containing a (meth)acrylic resin can be formed by coating a composition containing a (meth)acrylic resin on a polarizer, and then heating or irradiating with active energy rays, or by coating a composition containing a (meth)acrylic resin on a substrate film, and then heating or irradiating with active energy rays. In the latter case, a polarizer may be formed on the layer containing a (meth)acrylic resin.

[0054] The (meth)acrylic resin refers to a polymer in which a monomer having a (meth)acryloyl group is the main component among the monomers constituting the (meth)acrylic resin. Here, the main component refers to the monomer with the largest content (mass%) among the monomer components constituting the (meth)acrylic resin. By using a (meth)acrylic resin as a material for forming the protective layer, it is possible to suppress the deterioration of the optical properties of the circularly polarizing plate even in a humid and hot environment.

[0055] The (meth)acrylic resin is preferably a polymer of a photopolymerizable monomer, and may be, for example, a polymer of a monofunctional monomer or a polyfunctional monomer having a (meth)acryloyl group, either alone or in combination of two or more kinds. The (meth)acrylic resin may be a polymer of a monomer other than the monomer having a (meth)acryloyl group, for example, a monomer having a vinyl group.

[0056] The monomer having a (meth)acryloyl group is not particularly limited, but may be a compound having one or more (meth)acryloyl groups in the molecule, which may be used alone or in a mixture of two or more.Specific examples include dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ethylene oxide or propylene oxide added compounds of the above (meth)acrylates; oligoester(meth)acrylates having four or more (meth)acryloyl groups in the molecule, oligoether(meth)acrylates, oligourethane(meth)acrylates, oligoepoxy(meth)acrylates, oligomelamine(meth)acrylates, and polyfunctional acrylates having a dendrimer structure.

[0057] The thickness of the layer containing the (meth)acrylic resin is usually 0.1 μm or more, preferably 0.3 μm or more, and more preferably 0.5 μm or more, and is usually 20.0 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. When the thickness of the layer containing the (meth)acrylic resin is within the above range, a bendable circularly polarizing plate can be easily obtained.

[0058] The layer containing the aqueous resin can be formed by coating a composition containing the aqueous resin on a polarizer, and then heating or irradiating with active energy rays, or by coating a composition containing a (meth)acrylic resin on a substrate film, and then heating or irradiating with active energy rays. In the latter case, a polarizer may be formed on the layer containing the aqueous resin.

[0059] Examples of the aqueous resin include water-soluble polymers such as polyvinyl alcohol, ethylene-vinyl acetate copolymer, polyvinylpyrrolidone, starches, methyl cellulose, carboxymethyl cellulose, and sodium alginate, and among these, polyvinyl alcohol is preferred.

[0060] The thickness of the layer containing the aqueous resin is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 3 μm or less, more preferably 1.5 μm or less, and even more preferably 1 μm or less. When the thickness of the layer containing the aqueous resin is within the above range, a bendable circularly polarizing plate can be easily obtained.

[0061] The protective layer may be a single layer or may be formed of multiple layers. In an embodiment in which the protective layer is formed of multiple layers, the protective layer may be composed of a layer containing a (meth)acrylic resin and a layer containing a water-based resin.

[0062] <Retardation film> The circular polarizing plate of the present invention has a retardation film. The retardation film has a puncture modulus of 15 gf / mm or more, preferably 20 gf / mm or more, more preferably 25 gf / mm or more, and even more preferably 30 gf / mm or more. The upper limit of the puncture modulus of the retardation film is not particularly limited, and can be, for example, 200 gf / mm or less, or may be 50 gf / mm or less. A retardation film having a puncture modulus in such a range tends to be less susceptible to change in retardation value in a high temperature environment. The higher the puncture modulus, the less likely the retardation value is to change due to stress caused by dimensional shrinkage of the polarizing plate.

[0063] When the retardation film includes one retardation layer, the retardation film has a puncture modulus of 15 gf / mm or more, preferably 20 gf / mm or more, more preferably 25 gf / mm or more, and even more preferably 30 gf / mm or more. The upper limit of the puncture modulus of the retardation film is not particularly limited, and may be, for example, 200 gf / mm or less, 90 gf / mm or less, or 50 gf / mm or less.

[0064] When the retardation film includes two retardation layers, the retardation film has a puncture modulus of preferably 30 gf / mm or more, more preferably 40 gf / mm or more, even more preferably 50 gf / mm or more, and particularly preferably 70 gf / mm or more. The upper limit of the puncture modulus of the retardation film is not particularly limited, and may be, for example, 200 gf / mm or less, 150 gf / mm or less, or 100 gf / mm or less.

[0065] The puncture elastic modulus is a value obtained by dividing the force (gf) just before the retardation film breaks (or tears) when a needle (puncture tool) is punctured perpendicularly to the main surface of the retardation film by the strain (mm) at that time. A needle with a tip diameter of 1 mmφ and 0.5R can be used. The needle puncture speed can be 0.33 cm / sec. The puncture elastic modulus is measured by sandwiching the retardation film between two plates with a circular hole of 15 mm or less in diameter through which the needle can pass. The puncture elastic modulus can be measured in an environment at a temperature of 23°C. For example, the puncture elastic modulus can be measured for five retardation films, and the average value can be used as the puncture elastic modulus of the retardation film. A commercially available device can be used to measure the puncture elastic modulus. Examples of commercially available devices include the handy compression tester "KES-G5 Needle Penetration Force Measurement Specification" manufactured by Kato Tech Co., Ltd. and the small tabletop tester "EZ Test" manufactured by Shimadzu Corporation.

[0066] The puncture elastic modulus of the retardation film can be controlled by adjusting, for example, the type of polymerizable liquid crystal compound or alignment film used, the degree of curing of the polymerizable liquid crystal compound, the thickness of the retardation film, and the like.

[0067] The retardation film has a retardation layer. The retardation layer preferably has a layer composed of a composition containing a polymerizable liquid crystal compound. The layer composed of the composition containing the polymerizable liquid crystal compound specifically means a layer in which the polymerizable liquid crystal compound is cured. In this specification, a layer that gives a retardation of λ / 2, a layer that gives a retardation of λ / 4 (positive A layer), a positive C layer, etc. may be collectively referred to as a retardation layer. Further, the retardation film may contain an alignment film described later.

[0068] The layer that gives a retardation of λ / 2 preferably means a layer having an in-plane retardation value of 200 to 280 nm at a wavelength of 550 nm, and more preferably means a layer having an in-plane retardation value of 215 to 265 nm. The layer that gives a retardation of λ / 4 preferably means a layer having an in-plane retardation value of 100 to 160 nm at a wavelength of 550 nm, and more preferably means a layer having an in-plane retardation value of 110 to 150 nm. The positive C layer can be a layer showing a refractive index relationship of nx≒ny < nz. The retardation value in the thickness direction of the positive C layer can be -50 nm to -150 nm at a wavelength of 550 nm, and can be -70 nm to -120 nm.

[0069] The layer in which the polymerizable liquid crystal compound is cured is formed, for example, on an alignment film provided on a substrate. The substrate has a function of supporting the alignment film and may be a substrate formed in a long shape. This substrate functions as a release support and can support the retardation layer for transfer. Further, it is preferable that its surface has an adhesive force such that peeling is possible. Examples of the substrate include the resin films exemplified as the material of the protective film.

[0070] The thickness of the substrate is not particularly limited, but it is preferably in the range of, for example, 20 μm or more and 200 μm or less. When the thickness of the substrate is 20 μm or more, strength is imparted. On the other hand, when the thickness is 200 μm or less, an increase in processing scraps and wear of the cutting blade can be suppressed when the substrate is cut into individual substrates.

[0071] The substrate may be subjected to various anti-blocking treatments. Examples of the anti-blocking treatment include an easy-adhesion treatment, a treatment for kneading a filler or the like, and an embossing (knurling) treatment. By subjecting the substrate to such an anti-blocking treatment, it is possible to effectively prevent the substrates from sticking to each other when the substrates are wound up, that is, blocking, and it is possible to manufacture the optical film with high productivity.

[0072] The layer of the cured polymerizable liquid crystal compound is formed on the substrate via the alignment film. That is, the substrate and the alignment film are laminated in this order, and the layer of the cured polymerizable liquid crystal compound is laminated on the alignment film.

[0073] The alignment film is not limited to a vertical alignment film, and may be an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound horizontally, or may be an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound at an angle. The alignment film is preferably one that has solvent resistance that does not dissolve the composition containing the polymerizable liquid crystal compound described later by coating, etc., and also has heat resistance in the heat treatment for removing the solvent and orienting the liquid crystal compound. Examples of the alignment film include an alignment film containing an orienting polymer, a photoalignment film, and a groove alignment film that forms a concave-convex pattern or a plurality of grooves on the surface to provide alignment. The thickness of the alignment film is usually in the range of 10 nm to 10,000 nm, preferably in the range of 10 nm to 1000 nm, more preferably in the range of 500 nm or less, and even more preferably in the range of 10 nm to 200 nm. When the retardation film has an alignment film, increasing the thickness of the alignment film makes it easier to increase the puncture elastic modulus.

[0074] The resin used for the alignment film is not particularly limited as long as it is a resin used as a material for known alignment films, and a cured product obtained by curing a conventionally known monofunctional or polyfunctional (meth)acrylate monomer under a polymerization initiator, etc., can be used. Specifically, examples of the (meth)acrylate monomer include 2-ethylhexyl acrylate, cyclohexyl acrylate, diethylene glycol mono 2-ethylhexyl ether acrylate, diethylene glycol monophenyl ether acrylate, tetraethylene glycol monophenyl ether acrylate, trimethylolpropane triacrylate, lauryl acrylate, lauryl methacrylate, isobornyl acrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxypropyl acrylate, benzyl acrylate, tetrahydrofurfuryl methacrylate, 2-hydroxyethyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, methacrylic acid, and urethane acrylate. The resin may be one of these, or a mixture of two or more of them.

[0075] The type of polymerizable liquid crystal compound used in this embodiment is not particularly limited, but can be classified into rod-shaped type (rod-shaped liquid crystal compound) and discotic type (discotic liquid crystal compound) based on their shape. Each type can be further classified into low molecular type and high molecular type. Note that a high molecular weight generally refers to a material with a degree of polymerization of 100 or more (Polymer Physics, Phase Transition Dynamics, Masao Doi, page 2, Iwanami Shoten, 1992).

[0076] In this embodiment, any of the polymerizable liquid crystal compounds may be used. Furthermore, two or more kinds of rod-shaped liquid crystal compounds, two or more kinds of discotic liquid crystal compounds, or a mixture of rod-shaped and discotic liquid crystal compounds may be used.

[0077] As the rod-shaped liquid crystal compound, for example, those described in claim 1 of JP-T-11-513019 or those described in paragraphs

[0026] to

[0098] of JP-A-2005-289980 can be preferably used. As the discotic liquid crystal compound, for example, those described in paragraphs

[0020] to

[0067] of JP-A-2007-108732 or those described in paragraphs

[0013] to

[0108] of JP-A-2010-244038 can be preferably used.

[0078] Two or more kinds of polymerizable liquid crystal compounds may be used in combination. In that case, at least one kind has two or more polymerizable groups in the molecule. That is, the layer in which the polymerizable liquid crystal compound is hardened is preferably a layer formed by fixing a liquid crystal compound having a polymerizable group by polymerization. In this case, it is no longer necessary to show liquid crystallinity after the layer is formed.

[0079] The polymerizable liquid crystal compound has a polymerizable group capable of undergoing a polymerization reaction. As the polymerizable group, for example, a functional group capable of an addition polymerization reaction, such as a polymerizable ethylenically unsaturated group or a ring-polymerizable group, is preferable. More specifically, as the polymerizable group, for example, a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, etc. can be mentioned. Among them, a (meth)acryloyl group is preferable. Note that the (meth)acryloyl group is a concept that includes both a methacryloyl group and an acryloyl group.

[0080] The layer in which the polymerizable liquid crystal compound is cured can be formed by, for example, applying a composition containing the polymerizable liquid crystal compound onto an alignment film and irradiating it with active energy rays, as described below. The composition may contain components other than the above-mentioned polymerizable liquid crystal compound. For example, the composition preferably contains a polymerization initiator. The polymerization initiator used is selected from, for example, a thermal polymerization initiator or a photopolymerization initiator depending on the type of polymerization reaction. For example, photopolymerization initiators include α-carbonyl compounds, acyloin ethers, α-hydrocarbon-substituted aromatic acyloin compounds, polynuclear quinone compounds, and combinations of triaryl imidazole dimers and p-aminophenyl ketones. The amount of the polymerization initiator used is preferably 0.01 to 20% by mass, more preferably 0.5 to 5% by mass, based on the total solid content in the coating liquid.

[0081] In addition, the composition may contain a polymerizable monomer from the viewpoint of uniformity and strength of the coating film. Examples of the polymerizable monomer include radically polymerizable or cationic polymerizable compounds. Among them, polyfunctional radically polymerizable monomers are preferred.

[0082] The polymerizable monomer is preferably one that can be copolymerized with the above-mentioned polymerizable liquid crystal compound. The amount of the polymerizable monomer used is preferably 1 to 50% by mass, more preferably 2 to 30% by mass, based on the total mass of the polymerizable liquid crystal compound.

[0083] The composition may contain a surfactant from the viewpoint of uniformity and strength of the coating film. Examples of the surfactant include conventionally known compounds. Among them, fluorine-based compounds are particularly preferred.

[0084] The composition may contain a solvent, and an organic solvent is preferably used. Examples of organic solvents include amides (e.g., N,N-dimethylformamide), sulfoxides (e.g., dimethyl sulfoxide), heterocyclic compounds (e.g., pyridine), hydrocarbons (e.g., benzene, hexane), alkyl halides (e.g., chloroform, dichloromethane), esters (e.g., methyl acetate, ethyl acetate, butyl acetate), ketones (e.g., acetone, methyl ethyl ketone), and ethers (e.g., tetrahydrofuran, 1,2-dimethoxyethane). Among these, alkyl halides and ketones are preferred. Two or more organic solvents may be used in combination.

[0085] The composition may also contain various alignment agents, such as a vertical alignment promoter such as a polarizer interface side vertical alignment agent and an air interface side vertical alignment agent, and a horizontal alignment promoter such as a polarizer interface side horizontal alignment agent and an air interface side horizontal alignment agent. Furthermore, the composition may contain an adhesion improver, a plasticizer, a polymer, etc., in addition to the above components.

[0086] The active energy rays include ultraviolet rays, visible light, electron beams, and X-rays, and are preferably ultraviolet rays. Examples of the light source of the active energy rays include a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave excited mercury lamp, and a metal halide lamp.

[0087] The UV irradiation intensity is usually 100mW / cm 2 ~3,000mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a cationic polymerization initiator or a radical polymerization initiator. The ultraviolet irradiation time is usually 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and further preferably 0.1 seconds to 1 minute.

[0088] The ultraviolet light can be irradiated once or in multiple separate steps. It is preferable to irradiate the ultraviolet light multiple times. When the polymerization rate of the liquid crystal compound is increased, the puncture modulus is likely to be increased to within the range of the present invention. Although it depends on the polymerization initiator used, the integrated light amount at a wavelength of 365 nm is 700 mJ / cm. 2 More preferably, it is 1,100 mJ / cm or more. 2 More preferably, it is 1,300 mJ / cm or more. 2 It is more preferable that the integrated light amount is 2,000 mJ / cm or more. The integrated light amount is advantageous for increasing the polymerization rate of the polymerizable liquid crystal compound constituting the retardation film and increasing the puncture modulus of the retardation film. The integrated light amount at a wavelength of 365 nm is 2,000 mJ / cm or more. 2 It is preferable to set the dose to 1,800 mJ / cm or less. 2 It is more preferable that the integrated light amount is set to the above range. If the integrated light amount is set to the above range, there is a risk that the retardation film will be colored.

[0089] In addition, in order to prevent the alignment of the liquid crystal compound from being disturbed by heat immediately after the ultraviolet irradiation, it is preferable to provide a cooling step after the ultraviolet irradiation. By providing a cooling step after the ultraviolet irradiation, it is possible to suppress the alignment of the liquid crystal compound from being disturbed by heat generated immediately after the irradiation. As a result, the alignment degree of the liquid crystal compound is increased, and a film having higher rigidity can be obtained. The cooling temperature can be, for example, 20°C or less, and can be 10°C or less. The cooling time can be, for example, 10 seconds or more, and can be 20 seconds or more.

[0090] In this embodiment, the thickness of the retardation layer is preferably 0.5 μm or more. The thickness of the retardation layer is preferably 10 μm or less, more preferably 5 μm or less. The above upper limit and lower limit can be arbitrarily combined. When the thickness of the retardation layer is equal to or greater than the lower limit, sufficient durability can be obtained. When the thickness of the retardation layer is equal to or less than the upper limit, it can contribute to thinning of the circular polarizer. The thickness of the retardation layer can be adjusted so that the desired in-plane retardation value and thickness direction retardation value of the layer that gives a retardation of λ / 4, the layer that gives a retardation of λ / 2, or the positive C layer can be obtained.

[0091] The retardation film may include one layer of a cured polymerizable liquid crystal compound, or may include two or more layers of a cured polymerizable liquid crystal compound. When the retardation film includes two layers of a cured polymerizable liquid crystal compound, the two layers are preferably a layer that gives a retardation of λ / 4 and a positive C layer, or a layer that gives a retardation of λ / 4 and a layer that gives a retardation of λ / 2. When the retardation film includes two layers of a cured polymerizable liquid crystal compound, the retardation film may be manufactured by forming a layer of a cured polymerizable liquid crystal compound on an alignment film and laminating the two layers via an adhesive layer or a pressure-sensitive adhesive layer, or a layer of a cured polymerizable liquid crystal compound may be further formed on the layer of a cured polymerizable liquid crystal compound. After laminating the two layers, the substrate and the alignment film can be peeled off. The thickness of the retardation film is preferably 3 to 30 μm, more preferably 5 to 25 μm.

[0092] <Adhesive layer> The adhesive layer can be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be an active energy ray curable type or a heat curable type. The thickness of the adhesive layer is usually 3 to 30 μm, and preferably 3 to 25 μm.

[0093] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0094] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred.

[0095] <Front plate> The present invention includes a circular polarizing plate with a front plate, in which a circular polarizing plate and a front plate are laminated via an adhesive layer. The front plate is disposed on the viewing side of the polarizing plate. The front plate can be laminated to the polarizing plate via an adhesive layer. Examples of the adhesive layer include the above-mentioned pressure-sensitive adhesive layer and adhesive layer. As shown in Figures 2(a), (b), and (c), the front plate 4 can be laminated on the protective film 11 of the polarizing plate 1 via a pressure-sensitive adhesive layer 16.

[0096] Examples of the front plate include glass and resin film having a hard coat layer on at least one side. As the glass, for example, highly transparent glass or reinforced glass can be used. In particular, when a thin transparent surface material is used, chemically reinforced glass is preferable. The thickness of the glass can be, for example, 100 μm to 5 mm.

[0097] A front panel comprising a hard coat layer on at least one side of a resin film can have flexible properties, unlike the rigidity of existing glass. The thickness of the hard coat layer is not particularly limited, and may be, for example, 5 to 100 μm.

[0098] The resin film may be a film formed of a polymer such as a cycloolefin derivative having a unit of a monomer containing a cycloolefin such as norbornene or a polycyclic norbornene monomer, cellulose (diacetyl cellulose, triacetyl cellulose, acetyl cellulose butyrate, isobutyl ester cellulose, propionyl cellulose, butyryl cellulose, acetyl propionyl cellulose), ethylene-vinyl acetate copolymer, polycycloolefin, polyester, polystyrene, polyamide, polyetherimide, polyacrylic, polyimide, polyamideimide, polyethersulfone, polysulfone, polyethylene, polypropylene, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl acetal, polyether ketone, polyether ether ketone, polyethersulfone, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyurethane, or epoxy. The resin film may be an unstretched, uniaxially or biaxially stretched film. Each of these polymers may be used alone or in a mixture of two or more. As the resin film, preferred are polyamideimide film or polyimide film having excellent transparency and heat resistance, uniaxially or biaxially stretched polyester film, cycloolefin derivative film having excellent transparency and heat resistance and capable of handling large-sized films, polymethyl methacrylate film, and triacetyl cellulose and isobutyl ester cellulose films having no transparency and no optical anisotropy. The thickness of the resin film may be 5 to 200 μm, preferably 20 to 100 μm.

[0099] The hard coat layer can be formed by curing a hard coat composition containing a reactive material that forms a crosslinked structure by irradiation with light or heat energy. The hard coat layer can be formed by curing a hard coat composition containing a photocurable (meth)acrylate monomer or oligomer and a photocurable epoxy monomer or oligomer at the same time. The photocurable (meth)acrylate monomer can include one or more selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate. The epoxy (meth)acrylate can be obtained by reacting an epoxy compound with a carboxylic acid having a (meth)acryloyl group.

[0100] The hard coat composition may further include at least one selected from the group consisting of a solvent, a photoinitiator, and an additive. The additive may include at least one selected from the group consisting of inorganic nanoparticles, a leveling agent, and a stabilizer, and may further include components commonly used in the art, such as an antioxidant, a UV absorber, a surfactant, a lubricant, and an antifouling agent.

[0101] <Light blocking pattern> The light-shielding pattern may be provided as at least a part of a front panel or a bezel or a housing of a display device to which the front panel is applied. The light-shielding pattern may be formed on the display element side of the front panel. The light-shielding pattern may hide each wiring of the display device so that it is not visible to a user. The color and / or material of the light-shielding pattern is not particularly limited, and the light-shielding pattern may be formed of a resin material having various colors such as black, white, gold, etc. In one embodiment, the thickness of the light-shielding pattern may be in the range of 2 μm to 50 μm, preferably 4 μm to 30 μm, and more preferably 6 μm to 15 μm. In addition, in order to suppress the inclusion of air bubbles and the visibility of the boundary due to the step between the light-shielding pattern and the display part, a shape may be imparted to the light-shielding pattern.

[0102] <Method of manufacturing circularly polarizing plate> A method for producing a circular polarizing plate will be described using the circular polarizing plate 100 shown in Fig. 1(a) as an example. The circular polarizing plate 100 can be produced by laminating a polarizing plate 1 and a retardation film 2 with a pressure-sensitive adhesive layer 13 interposed therebetween.

[0103] The polarizing plate 1 can be manufactured by laminating the polarizer 10 and the protective films 11 and 12 with an adhesive layer interposed therebetween. The polarizing plate may be manufactured by preparing a long member, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and then laminating them together. After laminating the protective films 11 and 12 to the polarizer 10, a heating step or a humidity adjustment step may be performed.

[0104] The retardation film 2 can be manufactured, for example, as follows. An alignment film is formed on a substrate, and a coating liquid containing a polymerizable liquid crystal compound is applied onto the alignment film. In a state where the polymerizable liquid crystal compound is aligned, active energy rays are irradiated to harden the polymerizable liquid crystal compound. An adhesive layer 14 formed on a release film is laminated on the layer of hardened polymerizable liquid crystal compound. Next, the substrate and / or the alignment film is peeled off. Next, an adhesive layer 13 formed on a release film is laminated on a protective film 12. The retardation film 2 may be manufactured by preparing long members, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by laminating the respective members after cutting them into a predetermined shape.

[0105] Then, the release film laminated on the adhesive layer 13 is peeled off, and the retardation film 2 and the polarizing plate 1 are attached to each other via the adhesive layer 13, whereby the circularly polarizing plate 100 can be produced.

[0106] The color difference visually observed within the plane of the circular polarizer on the reflector after the heat resistance test can be reduced by uniforming the reflected hue within the plane of the circular polarizer after the heat resistance test. Elements necessary for uniforming the reflected hue within the plane of the circular polarizer after the heat resistance test include a uniform reflected hue within the plane of the circular polarizer before the heat resistance test and a small change in the reflected hue before and after the heat resistance test.

[0107] It is preferable that the reflection hue of the circular polarizer before the heat resistance test is uniform in-plane in order to reduce the reflection hue difference in the plane of the circular polarizer after the heat resistance test. Specifically, the magnitude of the difference between the reflection hue at the center (which may be the center of gravity or the center point 5 shown in FIG. 3) in the main surface before the heat resistance test and the reflection hue at a portion other than the center in the main surface (for example, the reflection hue at the point 5 other than the center shown in FIG. 3) is preferably 1.0 or less, more preferably 0.8 or less, and even more preferably 0.6 or less. The reflection hue difference between the center and other portions can be calculated, for example, from the following formula. Δa*b*=〔(Δa*) 2 +(Δb*) 2 〕 1 / 2 In the formula, Δa* is the difference between a* at the center and a* at the other parts, and Δb* is the corresponding difference in b*. If the uniformity of the reflection hue in the plane of the circular polarizer before the heat resistance test is low, the effect of improving visibility may be small even if the change in reflection hue before and after heat resistance is small. The heat resistance test can be performed, for example, by storing the circular polarizer in a dryer set at a temperature of 80° C. for 168 hours.

[0108] <Application> Circular polarizing plates can be used in various display devices. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic EL display devices, inorganic electroluminescence (hereinafter also referred to as inorganic EL) display devices, electron emission display devices (e.g., field emission display devices (FEDs) and surface field emission displays (SEDs)), electronic paper (display devices using electronic ink or electrophoretic elements, plasma display devices, projection display devices (e.g., grating light valve (GLV) display devices, display devices having digital micromirror devices (DMDs)), and piezoelectric ceramic displays. Liquid crystal display devices include both transmissive liquid crystal display devices and semi-transmissive liquid crystal display devices. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. Circular polarizing plates can be used particularly effectively in organic EL display devices or inorganic EL display devices.

[0109] 2(a) and 2(b), organic EL display devices 104 and 105 have a layered structure in which a circular polarizing plate is laminated on an organic EL display element 3 via an adhesive layer 14 laminated on a retardation film 20. EXAMPLES

[0110] (1) Film thickness measurement method The measurements were made using a digital micrometer, MH-15M, manufactured by Nikon Corporation.

[0111] (2) Measurement method of phase difference value The measurement was performed using a phase difference measuring device KOBRA-WPR (manufactured by Oji Scientific Instruments Co., Ltd.).

[0112] [Preparation of retardation film 1] Five parts of a photoalignment material (weight average molecular weight: 30,000) having the following structure was mixed with 95 parts of cyclopentanone (solvent), and the resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming an alignment film. [ka]

[0113] To 100 parts of a mixture of polymerizable liquid crystal compound A and polymerizable liquid crystal compound B shown below in a mass ratio of 90:10, 1.0 part of a leveling agent (F-556; manufactured by DIC Corporation) and 6 parts of a polymerization initiator, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure 369 (Irg369)", manufactured by BASF Japan Ltd.) were added.

[0114] Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration became 13%, and the mixture was stirred at 80° C. for 1 hour to obtain a liquid crystal cured film-forming composition.

[0115] Polymerizable liquid crystal compound A was produced by the method described in JP-A-2010-31223. Polymerizable liquid crystal compound B was produced according to the method described in JP-A-2009-173893. The molecular structures of each compound are shown below.

[0116] (Polymerizable liquid crystal compound A) [ka]

[0117] (Polymerizable liquid crystal compound B) [ka]

[0118] [Production of a laminate consisting of a substrate, an alignment film, and a layer of a cured polymerizable liquid crystal compound] A 50 μm thick cycloolefin resin film (trade name "ZF-14-50" manufactured by Zeon Corporation) was subjected to corona treatment as a substrate. The composition for forming an alignment film was applied to the corona-treated surface using a bar coater. The coating film was dried at 80°C for 1 minute. The dried coating film was irradiated with polarized UV at an axial angle of 45° using a polarized UV irradiation device (trade name "SPOT CURE SP-9" manufactured by Ushio Inc.) to obtain an alignment film. The polarized UV irradiation was performed with an integrated light amount of 100 mJ / cm at a wavelength of 313 nm. 2 It was carried out so that

[0119] Next, a liquid crystal cured film-forming composition was applied onto the alignment film using a bar coater. The applied film was dried at 120°C for 1 minute. The dried applied film was irradiated with ultraviolet light using a high-pressure mercury lamp (trade name: "Uniquer VB-15201BY-A" by Ushio Inc.). The ultraviolet light irradiation process was carried out with an integrated light amount of 250 mJ / cm at a wavelength of 365 nm. 2 Immediately after irradiation, the cured film was placed in an oven set at 5° C. for 20 seconds as a cooling step. Immediately after removal from the oven, the ultraviolet irradiation step and cooling step were carried out again to obtain a laminate consisting of the substrate, the alignment film, and a layer of cured polymerizable liquid crystal compound.

[0120] (Measurement of phase difference value) An adhesive layer was laminated on the layer of the laminate where the polymerizable liquid crystal compound was cured. The laminate was attached to glass via the adhesive layer. Thereafter, the substrate of the laminate was peeled off to obtain a sample for evaluating the retardation value. As a result, the layer where the polymerizable liquid crystal compound was cured had retardation values ​​Re(λ) at each wavelength of Re(450)=121 nm, Re(550)=142 nm, and Re(650)=146 nm. As a result, Re(450) / Re(550)=0.85 and Re(650) / Re(550)=1.03 were calculated. The layer where the polymerizable liquid crystal compound was cured was a layer that gave a retardation of λ / 4.

[0121] (Measurement of puncture elasticity) The puncture modulus was measured as follows. A needle was attached to a handy compression tester "KES-G5 Needle Penetration Force Measurement Specification" manufactured by Kato Tech Co., Ltd. The needle was pierced perpendicularly into the main surface of the laminate from which the substrate had been peeled off, which was fixed between two plates with a circular hole of 11 mm in diameter, and the force (gf) just before the film broke was divided by the strain (mm) at that time to calculate the value. This operation was performed on five retardation films (samples for puncture test), and the average value was taken as the puncture modulus of the retardation film. The needle used had a tip diameter of 1 mmφ and 0.5R. The needle was pierced at a speed of 0.33 cm / sec. The puncture modulus of retardation film 1 is shown in Table 1.

[0122] [Preparation of retardation film 2] The cumulative amount of ultraviolet light irradiated when curing the coating film of the liquid crystal cured film-forming composition is 400 mJ / cm at a wavelength of 365 nm. 2 (That is, the total cumulative light intensity of the two UV irradiations is 800 mJ / cm 2 A laminate including the retardation film 2 was produced in the same manner as in [Production of Retardation Film 1], except that the thickness of the retardation film 2 was 100 μm or more. The puncture elastic modulus of the retardation film 2 was measured in the same manner as above. The puncture elastic modulus of the retardation film 2 is shown in Table 1.

[0123] [Preparation of retardation film 3] The cumulative amount of ultraviolet light irradiated when curing the coating film of the liquid crystal cured film-forming composition is 600 mJ / cm at a wavelength of 365 nm. 2 (That is, the total cumulative light intensity of the two UV irradiations is 1200 mJ / cm 2 A laminate including the retardation film 3 was produced in the same manner as in [Production of Retardation Film 1], except that the thickness of the retardation film 3 was 100 μm or more. The puncture elastic modulus of the retardation film 3 was measured in the same manner as above. The puncture elastic modulus of the retardation film 3 is shown in Table 1.

[0124] [Preparation of retardation film 4] The cumulative amount of ultraviolet light irradiated when curing the coating film of the liquid crystal cured film-forming composition is 800 mJ / cm at a wavelength of 365 nm. 2 (That is, the total cumulative light intensity of the two UV irradiations is 1600 mJ / cm 2 A laminate including the retardation film 4 was produced in the same manner as in [Production of Retardation Film 1], except that the thickness of the retardation film 4 was 100 μm or more. The puncture elastic modulus of the retardation film 4 was measured in the same manner as above. The puncture elastic modulus of the retardation film 4 is shown in Table 1.

[0125] [Creation of retardation film 5] As a composition for forming a vertical alignment film, 5 parts by weight of Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), which is a commercially available alignment polymer, and 95 parts by weight of methyl ethyl ketone (solvent) were mixed to obtain a composition for forming a vertical alignment film.

[0126] As a composition for forming a vertically aligned retardation layer, 20 parts by weight of a photopolymerizable nematic liquid crystal compound (RMM28B manufactured by Merck) and 1 part by weight of Irgacure 907 (Irg-907 manufactured by BASF) as a photopolymerization initiator were dissolved in 80 parts by weight of propylene glycol monomethyl ether acetate to prepare a coating liquid for forming a vertically aligned retardation layer.

[0127] A 50 μm thick cycloolefin resin film (trade name "ZF-14-50" manufactured by Zeon Corporation) was subjected to corona treatment as a substrate. The composition for forming a vertical alignment film was applied to the corona treated surface with a bar coater. The applied film was heated at 100° C. for 120 seconds and cured to form a vertical alignment film.

[0128] A coating solution for forming a vertical alignment retardation layer was applied onto the previously obtained vertical alignment film, and the coating film was heated at a temperature of 80° C. for 60 seconds. Thereafter, ultraviolet rays (UVB) were irradiated at an integrated light intensity of 220 mJ / cm 2 2Irradiate so as to obtain the following, polymerize and cure the composition for forming a vertically aligned retardation layer, and form a vertically aligned retardation layer with a thickness of 0.7 μm on the vertically aligned film. When the retardation value at a wavelength of 550 nm of the obtained vertically aligned retardation layer was measured, Re(550) = 1 nm and Rth(550) = -75 nm. That is, the vertically aligned retardation layer was a positive C layer satisfying the relationship of nx ≒ ny < nz. Note that since the retardation value of the cycloolefin-based resin film as the substrate at a wavelength of 550 nm is substantially 0, it does not affect the optical properties of the vertically aligned retardation layer.

[0129] Subsequently, a layer that provides a retardation of λ / 4 was formed on the obtained vertically aligned retardation layer in the same manner as [Production of Retardation Film 2], and a laminate including a retardation film 5 was produced. In this way, a laminate including a retardation film 5 in which a substrate, a vertically aligned film, a positive C layer, an alignment film, and a layer that provides a retardation of λ / 4 were laminated in this order was produced. In the same manner as above, the puncture elastic modulus of the retardation film 5 was measured. The puncture elastic modulus of the retardation film 5 is shown in Table 1.

[0130] [Table 1]

[0131] [Preparation of Adhesive Layer] Adhesive A: A sheet-like adhesive with a thickness of 5 μm (“NCF #L2” manufactured by Lintec Corporation) Adhesive B: A sheet-like adhesive with a thickness of 25 μm (“P-3132” manufactured by Lintec Corporation)

[0132] [Preparation of Protective Film] Protective Film A: A film in which a hard coat layer with a thickness of 3 μm was formed on a stretched film made of a norbornene-based resin with a thickness of 25 μm [Product name “COP25ST-HC” manufactured by Nippon Paper Industries Co., Ltd. Protective Film B: A triacetyl cellulose film with a thickness of 20 μm [Product name “ZRG20SL” manufactured by Fujifilm Corporation] Protective Film C: An unstretched film made of triacetyl cellulose with a thickness of 25 μm

[0133] [Making the front panel] A front panel having hard coat layers on both sides of a substrate film was prepared. The substrate film was a polyimide film having a thickness of 50 μm, and the hard coat layers had a thickness of 10 μm.

[0134] [Example 1] [Preparation of polarizing plate] A 20 μm thick polyvinyl alcohol film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched about 4 times by dry stretching, and then, while maintaining tension, was immersed in pure water at 40° C. for 40 seconds, and then immersed in an aqueous solution having a weight ratio of iodine / potassium iodide / water of 0.052 / 5.7 / 100 at 28° C. for 30 seconds to perform a dyeing treatment. Then, it was immersed in an aqueous solution having a weight ratio of potassium iodide / boric acid / water of 11.0 / 6.2 / 100 at 70° C. for 120 seconds. After washing with pure water at 8° C. for 15 seconds, it was dried at 60° C. for 50 seconds and then at 75° C. for 20 seconds while maintaining a tension of 300 N, to obtain a 7 μm thick polarizer in which iodine was adsorbed and aligned in the polyvinyl alcohol film.

[0135] A water-based adhesive was applied to one surface of the polarizer, and protective film A was attached thereto so that the stretching direction of protective film A was at an angle of 45 degrees to the absorption axis of the polarizer. A water-based adhesive was applied to the other surface of the polarizer, and a protective film B was attached thereto. The resultant was then dried to obtain a polarizing plate. The water-based adhesive was prepared by dissolving 3 parts of carboxyl-modified polyvinyl alcohol (trade name "KL-318" available from Kuraray Co., Ltd.) in 100 parts of water, and adding 1.5 parts of a polyamide epoxy-based additive, which is a water-soluble epoxy resin (trade name "Sumirez Resin 650(30)" available from Taoka Chemical Co., Ltd., an aqueous solution with a solid content of 30%).

[0136] Adhesive A was laminated on the layer of the cured polymerizable liquid crystal compound in the laminate prepared in [Preparation of Retardation Film 2]. Next, the substrate was peeled off from the laminate, and adhesive B was laminated on the surface exposed by the peeling. In this way, retardation film 2 with double-sided adhesives, consisting of adhesive A, the layer of the cured polymerizable liquid crystal compound, the alignment film, and adhesive B, was prepared.

[0137] [Preparation of circular polarizing plate] The retardation film 2 with double-sided adhesive was attached to the protective film B of the polarizing plate via the adhesive A of the retardation film 2 with double-sided adhesive. The slow axis of the layer in which the polymerizable liquid crystal compound was cured was at 45 degrees to the absorption axis of the polarizer and at 90 degrees to the stretching direction of the protective film A. In this manner, a circular polarizing plate consisting of the protective film A, the aqueous adhesive layer, the polarizer, the aqueous adhesive layer, the protective film B, the adhesive A, the layer in which the polymerizable liquid crystal compound was cured, the alignment film, and the adhesive B was produced.

[0138] The circular polarizing plate was cut into a rectangle of 140 mm x 70 mm so that the slow axis of the layer in which the polymerizable liquid crystal compound was cured was parallel to the long side. At this time, the stretching direction of the protective film A was parallel to the short side direction. The cut circular polarizing plate was attached to a glass plate (manufactured by Corning, product number: EAGLE XG (registered trademark)) having a thickness of 0.4 mm via adhesive B. In this manner, samples for evaluation were prepared.

[0139] [Example 2] A circularly polarizing plate was prepared in the same manner as in Example 1, except that the laminate prepared in [Preparation of Retardation Film 3] was used instead of the laminate prepared in [Preparation of Retardation Film 2] in Example 1, and a sample for evaluation was prepared.

[0140] [Example 3] A circularly polarizing plate was prepared in the same manner as in Example 1, except that the laminate prepared in [Preparation of Retardation Film 4] was used instead of the laminate prepared in [Preparation of Retardation Film 2] in Example 1, and a sample for evaluation was prepared.

[0141] [Example 4] (Comparative) A circularly polarizing plate was produced in the same manner as in Example 2, and a sample for evaluation was produced, except that protective film A was attached to the polarizer so that the slow axis of the layer in which the polymerizable liquid crystal compound was cured was at an angle of 45 degrees to the absorption axis of the polarizer and 0 degrees to the stretching direction of protective film A. In this case, the stretching direction of protective film A was parallel to the long side direction.

[0142] [Example 5] A circularly polarizing plate was prepared in the same manner as in Example 1, except that the laminate prepared in [Preparation of Retardation Film 5] was used instead of the laminate prepared in [Preparation of Retardation Film 2] in Example 1, and a sample for evaluation was prepared.

[0143] [Example 6] A circular polarizing plate was produced in the same manner as in Example 1, except that the protective film B was not laminated when the polarizing plate was produced. Furthermore, the adhesive layer B was laminated on the protective film A. The front plate and the circular polarizing plate were bonded together via the adhesive layer B. In this manner, a circular polarizing plate was produced, which was composed of the front plate, the adhesive layer B, the protective film A, the aqueous adhesive layer, the polarizer, the adhesive A, the layer of the cured polymerizable liquid crystal compound, the alignment film and the adhesive B. Furthermore, a sample for evaluation was produced in the same manner as in Example 1.

[0144] [Example 7] [Surface treatment layer forming composition] The following components were mixed to prepare a composition for forming a surface treatment layer. 2.0 parts by mass of dendrimer acrylate having 18 functional acrylic groups (Miramer SP1106, Miwon Co., Ltd.), 10.0 parts by mass of urethane acrylate having hexafunctional acrylic groups (Miramer PU-620D, Miwon Co., Ltd.), 8.0 parts by mass of an acrylate monomer having a trifunctional acrylic group (M340, Miwon Co., Ltd.), Photopolymerization initiator (Irgacure-184, BASF) 2 parts by mass, Leveling agent (BYK-3530, BYK) 0.1 parts by weight, Methyl ethyl ketone (MEK) 77.9 parts by weight

[0145] [Polarizer forming composition] (Polymerizable liquid crystal compound) The polymerizable liquid crystal compound used was a polymerizable liquid crystal compound represented by formula (1-6) [hereinafter also referred to as compound (1-6)] and a polymerizable liquid crystal compound represented by formula (1-7) [hereinafter also referred to as compound (1-7)]. [ka] [ka]

[0146] Compounds (1-6) and (1-7) were synthesized according to the method described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).

[0147] (dichroic dye) As the dichroic dye, azo dyes represented by the following formulae (2-1a), (2-1b), and (2-3a) and described in the examples of JP-A-2013-101328 were used. [ka] [ka] [ka]

[0148] A composition for forming a polarizing layer was prepared by mixing 75 parts of compound (1-6), 25 parts of compound (1-7), 2.5 parts of each of the azo dyes represented by the above formulas (2-1a), (2-1b), and (2-3a) as dichroic dyes, 6 parts by weight of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure369, manufactured by BASF Japan) as a polymerization initiator, and 1.2 parts of a polyacrylate compound (BYK-361N, manufactured by BYK-Chemie) as a leveling agent in 400 parts of toluene as a solvent, and stirring the resulting mixture at 80° C. for 1 hour.

[0149] The above-mentioned composition for forming a surface treatment layer was applied to the protective film A. The coating film was dried at 80° C. for 5 minutes, and then exposed to light at a dose of 500 mJ / cm 2 using a UV irradiation device. 2 The coating was cured by irradiating it with ultraviolet light so that the wavelength was 365 nm (standard wavelength). The UV irradiation device used was SPOT CURE SP-7 manufactured by Ushio Inc. The thickness of the surface treatment layer was 10.0 μm.

[0150] The composition for forming an alignment film used in the preparation of the retardation film 1 was applied by bar coating onto the surface treatment layer of the protective film A. The coating film was dried at 80°C for 1 minute. The coating film was then irradiated with polarized UV light using the above-mentioned UV irradiation device and wire grid to impart alignment properties to the coating film. The exposure dose was 100 mJ / cm. 2 (Based on 365 nm). UIS-27132## (manufactured by Ushio Inc.) was used as the wire grid. In this manner, an alignment film was formed. The thickness of the alignment film was 100 nm.

[0151] The above-mentioned composition for forming a polarizer was applied onto the formed alignment film by a bar coating method. The coating film was dried by heating at 100° C. for 2 minutes and then cooled to room temperature. Using the above-mentioned UV irradiation device, an accumulated light amount of 1200 mJ / cm 2The coating film was irradiated with ultraviolet light at 365 nm (standard wavelength) to form a polarizer. The thickness of the obtained polarizer was 3 μm. A composition containing polyvinyl alcohol and water was applied onto the polarizer so that the thickness after drying would be 0.5 μm, and the composition was dried at a temperature of 80° C. for 3 minutes to form a protective layer. In this manner, a polarizing plate consisting of protective film A, a surface treatment layer, an alignment film, a polarizer, and a protective layer was produced.

[0152] Except for using the above polarizing plate, a circular polarizing plate was produced and an evaluation sample was prepared in the same manner as in Example 6. The evaluation sample had a front plate, pressure-sensitive adhesive layer B, protective film A, a surface treatment layer, an alignment film, a polarizer, a protective layer, pressure-sensitive adhesive A, a layer of a cured polymerizable liquid crystal compound, an alignment film, and pressure-sensitive adhesive B in this order.

[0153] [Example 8] A circular polarizing plate was produced in the same manner as in Example 7, except that protective film C was used instead of the laminate of protective film A and surface treatment layer, and an evaluation sample was produced. The evaluation sample had a front plate, pressure-sensitive adhesive layer B, protective film C, an alignment film, a polarizer, a protective layer, pressure-sensitive adhesive A, a layer of a cured polymerizable liquid crystal compound, an alignment film, and pressure-sensitive adhesive B in this order.

[0154] [Example 9] Except for not laminating a front panel, a circularly polarizing plate was produced and an evaluation sample was produced in the same manner as in Example 8. The evaluation sample had a protective film C, an alignment film, a polarizer, a protective layer, pressure-sensitive adhesive A, a layer of a cured polymerizable liquid crystal compound, an alignment film, and pressure-sensitive adhesive B in this order.

[0155] [Comparative Example 1] A circularly polarizing plate was prepared in the same manner as in Example 1, except that the laminate prepared in [Preparation of Retardation Film 1] was used instead of the laminate prepared in [Preparation of Retardation Film 2] in Example 1, and a sample for evaluation was prepared.

[0156] [Color evaluation before and after heat resistance test] As a reflector, we prepared MIRO (5011GP) manufactured by ALANOD Co., Ltd. This reflector is a specular reflector having a reflective surface formed by vapor deposition.

[0157] The evaluation sample was placed on the reflector. The reflection hue (a*, b*) was measured using a spectrophotometer (Konica Minolta Japan, Inc., product name: CM-2600d). The reflection hue was a value when the light source was D65, and was measured using the SCI method (including regular reflection light).

[0158] Specifically, the measurement points were points 5 shown in Fig. 3. The nine points 5 shown in Fig. 3 are points in an area 5 mm inward from the edge of the circular polarizing plate, and are positioned at intervals of approximately 30 mm along the short side and approximately 65 mm along the long side.

[0159] The evaluation samples prepared in Examples 1 to 9 and Comparative Example 1 were measured for reflected hue before and after storage in a dryer at 80°C for 168 hours. The absolute value of the hue change Δa*b* at each point was calculated. The hue change value at each point was calculated based on the direction of the hue change, and the difference between the maximum and minimum hue change values ​​of each evaluation sample was taken as Δa*b*(MAX-MIN). The results are shown in Tables 2 and 3.

[0160] Δa*=a*(after heat resistance test)-a*(before heat resistance test) Δb*=b*(after heat resistance test)-b*(before heat resistance test) Δa*b*=〔(Δa*) 2 +(Δb*) 2 〕 1 / 2 The hue change value was taken as Δa*b* when Δa* was 0 or more, and was taken as Δa*b*×−1 when Δa* was less than 0.

[0161] [Table 2]

[0162] [Table 3] [Industrial Applicability]

[0163] INDUSTRIAL APPLICABILITY The present invention is useful because it can provide a circular polarizing plate having a retardation film and which shows little change in hue before and after placement in a high-temperature environment. [Explanation of symbols]

[0164] 1 Polarizing plate 2 Phase contrast film 3. Organic EL display element 4 Front plate 5 points 10 Polarizer 11,12 Protective film 13, 14, 16 Adhesive layer 15 Adhesive layer 20,21 Layer of hardened polymerizable liquid crystal compound 100,101,102,103 Circular polarizing plate 104,105,106 Organic EL display device

Claims

1. A circularly polarizing plate in which a polarizing plate and a retardation film are laminated via an adhesive layer, the circularly polarizing plate has a pressure-sensitive adhesive layer on a surface thereof, The polarizing plate has a polarizer, the retardation film is disposed between the polarizing plate and the pressure-sensitive adhesive layer, The retardation film includes two retardation layers, The retardation layer includes a layer in which a polymerizable liquid crystal compound is hardened, The retardation film has a puncture elastic modulus of 30 gf / mm or more and 150 gf / mm or less, The circular polarizer has a substantially rectangular shape, The puncture elastic modulus is an elastic modulus measured in a test using a needle with a tip diameter of 1 mmφ and 0.5R at a puncture speed of 0.33 cm / sec, and the test is performed in a state where the retardation film is fixed between two plates with a circular hole with a diameter of 11 mm.

2. 2. The circular polarizing plate according to claim 1, wherein the polarizer has a thickness of 15 μm or less.

3. 3. The circularly polarizing plate according to claim 1, wherein the retardation film has a thickness of 25 μm or less.

4. 4. The circularly polarizing plate according to claim 1, wherein the polarizer is formed from a layer of a cured liquid crystal compound.

5. 5. A circularly polarizing plate with a front plate, comprising the circularly polarizing plate according to claim 1 and a front plate laminated together via an adhesive layer.

6. A display device comprising the circularly polarizing plate according to any one of claims 1 to 4 laminated on a display element via the pressure-sensitive adhesive layer.

Citation Information

Patent Citations

  • Optical element with homeotropically aligned liquid crystal molecule, and base for liquid crystal display and liquid crystal display using the optical element

    JP2006284968A

  • Liquid crystal panel and polarizing plate with retardation layer

    JP2009186830A

  • Optical film

    JP2015163935A

  • Optical film and production method of optical film

    JP2015191143A

  • Method for manufacturing optical laminate, optical laminate, optically anisotropic laminate, circularly polarizing plate, and organic electroluminescence display device

    JP2016224128A